Nurses and palliative care in oncology: an integrative literature review (Research, Society and Development, 2021)
This is an integrative review whose objective is to analyze articles on Nurse Preparation against palliative cancer patients in the last five years. The survey was performed in the LILACS and SciELO databases, in August 2019. After applying the inclusion and exclusion criteria, five articles were selected for full analysis. As a result, most of the journals used were from nursing, where their focuses were: palliative care in intensive care, palliative care for the elderly, nurses' understanding of palliative care, knowledge of nursing students regarding palliative care and the feelings involved in palliative care. assistance. It was found that it is pertinent to conduct research that addresses the preparation of nurses in relation to palliative cancer patients and the correlation between technique and emotional support.